It's more than just a bond: nurses and parents are great hospital business - Degl, Jennifer; Discenza, Deb; Eklund, Wakako; Kenner, Carole (Frontiers in Pediatrics, 2024)
A newborn's admission to the Neonatal Intensive Care Unit (NICU) can be both stress inducing and frightening for a parent or caregiver. With nursing being a constant calming presence, a trusting bond between the parents and nurses often becomes the lifeline to survive the NICU journey. This bond impacts not only the baby and family, but also promotes the institution's reputation within the community. In today's climate of healthcare professional shortages, the power of the nurses' connections to families cannot be overlooked. It is critical in all neonatal units, especially where parents are being approached to enroll their infant in clinical research.